Analisis Akad Mukhabarah terhadap Kerjasama antara Pesantren dengan Kelompok Tani - Lubia Nasta Bila (UPT Publikasi Ilmiah Unisba, 2023)
waqf was carried out in a productive manner as was done by Umar bin Khattab ra. This is the basis for the management of the Danul Falah Islamic Boarding School, Pangalengan District, which has a waqf asset in the form of vacant land which is managed productively through a form of cooperation with the Hikmah Farmers Group. Technically this form of cooperation is like a mukhabarah contract, but there are still some indicators of its implementation, such as a muzaraah contract. Based on these problems, the focus of the research is formulated in the form of questions as follows: How is the implementation of productive waqf land management cooperation between the Hikmah Farmers' group and the Danul Falah Islamic Boarding School? And what is the analysis of the mukhabarah contract on the implementation of productive waqf land management collaboration between the Hikmah Farmers' group and the Danul Falah Islamic Boarding School? This study uses an analytical descriptive method with a normative juridical approach. The results showed that the implementation of productive waqf land management cooperation between the Hikmah Farmers Group and the Danul Falah Islamic Boarding School in Pangalengan District used a cooperation contract that was in line with the mukhabarah contract and its implementation was in accordance with the provisions of the mukhabarah contract according to fiqh muamalah. wakaf dilakukan dengan cara dikelola secara produktif seperti yang dilakukan Umar bin Khattab ra.. Hal ini menjadi dasar bagi manajemen Pesantren Danul Falah Kecamatan Pangalengan yang memiliki asset wakaf berupa lahan kosong yang dikelola secara produktif melalui bentuk kerjasama dengan Kelompok Tani Hikmah. Secara teknis bentuk kerjasama tersebut seperti akad mukhabarah, akan tetapi masih terdapat beberapa indikator pelaksanaannya seperti akad muzaraah. Berdasarkan permasalahan tersebut, maka fokus penelitian dirumuskan ke dalam bentuk pertanyaan sebagai berikut: Bagaimana pelaksanaan kerjasama pengelolaan lahan wakaf produktif antara kelompok Tani Hikmah dengan Pesantren Danul Falah? Dan bagaimana analisis akad mukhabarah terhadap terhadap pelaksanaan kerjasama pengelolaan lahan wakaf produktif antara kelompok Tani Hikmah dengan Pesantren Danul Falah? Penelitian ini menggunakan metode deskriptif analitis dengan pendekatan yuridis normative. Hasil penelitian menunjukkan bahwa pelaksanaan kerjasama pengelolaan lahan wakaf produktif antara Kelompok Tani Hikmah dengan Pesantren Danul Falah Kecamatan Pangalengan menggunakan akad kerjasama yang sejalan dengan akad mukhabarah dan pelaksanaanya sesuai dengan ketentuan akad mukhabarah menurut fikih muamalah.